Magnetic Resonance Imaging and Bioluminescence Imaging for Evaluating Tumor Burden in Orthotopic Colon Cancer - Ravoori, M. K. (Sci Rep, 2019)
Quantifying tumor burden is important for following the natural history of orthotopic colon cancer and therapeutic efficacy. Bioluminescence imaging (BLI) is commonly used for such assessment and has both advantages and limitations. We compared BLI and magnetic resonance imaging (MRI) for quantifying orthotopic tumors in a mouse model of colon cancer. Among sequences tested, T2-based MRI imaging ranked best overall for colon cancer border delineation, contrast, and conspicuity. Longitudinal MRI detected tumor outside the colon, indistinguished by BLI. Colon tumor weights calculated from MRI in vivo correlated highly with tumor weights measured ex vivo whereas the BLI signal intensities correlated relatively poorly and this difference in correlations was highly significant. This suggests that MRI may more accurately assess tumor burden in longitudinal monitoring of orthotopic colon cancer in this model as well as in other models.